(untitled) (The International Journal for Scientific Research, 2024)
The study aimed to explore the relationship between cognitive control strategies (proactive, reactive, balanced proactive, and balanced reactive) and creative thinking (convergent and divergent) among female secondary school students, considering the impact of the educational environment. To achieve this, the study adopted a descriptive-correlational approach and employed the AX-Continuous Performance Task (AX-CPT) along with measures of creative thinking (both convergent and divergent) on a sample of 139 students. The results revealed significant relationships between divergent thinking and cognitive control strategies, as well as an association between convergent thinking and specific cognitive control measures. The importance of balanced control emerged as a key factor in enhancing creative performance. Although clear statistical differences were absent between cognitive control strategies in both convergent and divergent thinking, the graphical analyses demonstrated variations in performance across schools and different control strategies. The findings showed that School Thirteen excelled in convergent thinking, while Dar Al-Ruwad School stood out in divergent thinking and its components (fluency, flexibility, and originality), reflecting the role of the school environment in fostering creativity. A significant scientific contribution of this study is the classification of the sample into four groups using the Proactive Bias Index (PBI), which illustrates cognitive control strategies along a psychological continuum extending from proactive to reactive, with balanced strategies in between. This classification provides an integrative framework for understanding the dynamics of cognitive control and its relationship with creative thinking. Accordingly, the study recommends developing flexible educational environments that promote balanced control strategies to enhance students’ creative thinking.